Hybrid breeding boosted molecular genetics in rye - R. Schlegel (Вавиловский журнал генетики и селекции)
History of rye (Secale cereale L.) breeding began from the first targeted selections made in Germany by the Probsteier Seed Cooperative around 1850, and over 150 years breeding yielded a tremendous amount of results. Rye has also long been used as cytological subject due to its low number of chromosomes and their size. However, genetic findings in rye up to the early 1980s were rather scant. About 120 genes could be assigned to seven linkage groups. Only through the development of new methods such as C-banding, in situ DNA hybridization, enzymology and molecular marker techniques achieved an enormous progress. Particularly, the latter was driven by agronomic success of hybrid breeding in rye. The basic genetic knowledge resulted from intra- and interspecies genetic diversity assay and phylogenetic studies in the genus Secale using nuclear and cytoplasmic molecular markers facilitated successful selection of parents for hybrid breeding and hence contributed to improvement of heterosis effects. Main achievements in rye hybrid breeding and genetic mechanisms exploited for different hybrid breeding strategies are discussed. The utilsation of landraces and wild relatives via advanced backcross procedures, combined by QTL analysis and introgression libraries, contributed to increase of heterotic effects. Those marker-assisted approaches became the basis of recent hybrid breeding of rye. Prediction of hybrid performance can also be improved significantly by marker-assisted selection and genomic selection based on genomewide marker data. The findings in rye genetics (including phylogenetic, mapping and population studies) are reviewed in their relation with the hybrid breeding purposes and demands. Overall, about 450 morphological and biochemical traits are mapped throughout the genome plus about 5,000 DNA markers. They are not only associated with individual chromosome or segments but also efficiently used for comparative mapping (evolutionary studies) introgression monitoring, QTL tagging, and marker-assisted selection.